Emergency Service and Patient Guidance, University of Buenos Aires. Buenos Aires, Argentina. Chair of Bucomaxillofacial Surgery and Traumatology I, University of Buenos Aires. Buenos Aires, Argentina - Cesar Gatti, Patricio (2023)
Objective: To evaluate the prevalence of dry socket as a postoperative complication in cases where there was intense local pain in the preoperative state, during the preventive mandatory social isolation (PMSI) for the COVID-19 pandemic in Argentina. Methods: This was a descriptive study, which included 1209 walk-in patients at the emergency and orientational service at Buenos Aires University School of Dentistry during the PMSI from March 20 to June 20, 2020, with indication for dental extraction as well as intense acute pain at the surgical site. The presence of dry socket was exploratoryly associated with the variables age, sex, smoking and chronic medication use. Results: 1209 patients were operated, resulting in a total 1372 dental extractions. Average patient age was 41 years. The prevalence found in this study was 1.06%. Conclusion: The prevalence of dry socket was 1%, not being higher than other experiences where pain was not considered a condition prior to extraction.